ANALISIS KREATIVITAS SISWA DALAM PEMBELAJARAN BERBASIS WEB (GOOGLE SITES) PADA MATA PELAJARAN DESAIN GRAFIS KELAS XI DI SMKN 1 GARUT - Firmansyah, Muhammad Lutfi; Yuniar Purwanti; Dudi Suprihadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the limited use of web-based learning media in Graphic Design instruction, which has hindered the optimal development of student creativity. Google Sites was selected as the learning medium because it presents material in an integrated, interactive, and easily accessible manner, thereby fostering a more effective learning process. The study aimed to assess student creativity levels before and after using Google Sites and to analyze the effectiveness of Google Sites on student creativity regarding Graphic Design topics for Grade XI students at SMKN 1 Garut. The study employed a quantitative approach using a quasi-experimental method with a Pretest-Posttest Control Group Design. The sample consisted of two classes: Class XI DKV 2 served as the experimental group (using Google Sites), and Class XI DKV 1 served as the control group (receiving conventional instruction), with 20 students in each class. Data collection involved pretests and posttests to measure student creativity, as well as questionnaires to gauge student responses to the use of Google Sites. Data analysis included tests for validity, reliability, normality, and homogeneity, alongside hypothesis testing using the Independent Sample t-test. The results indicate that the use of Google Sites enhanced student creativity in Graphic Design. This is evidenced by superior posttest results in the experimental group compared to the control group and hypothesis test results showing a significant difference between the two groups. Furthermore, questionnaire results revealed a positive student response to Google Sites, citing its ease of use, engaging nature, ability to facilitate material comprehension, and capacity to boost active participation and learning interest. In conclusion, the web-based learning medium Google Sites is effective for Graphic Design instruction and enhances the creativity of Grade XI students at SMKN 1 Garut. Therefore, Google Sites serves as a viable technology-based learning alternative to support a learning process that is interactive, innovative, and learner-centered.